OPTIMASI SENSORI, NUTRISI DAN KANDUNGANANTIOKSIDAN PADA CAMPURAN JUS BUAH - Umar Thoriq, Muh.
Indonesia's fruit production reaches 25,96 million tons per year. However, fruit consumption in Indonesia is still low. Processing fruit into fruit juice provides ease of consumption. Improving the quality of juice in terms of sensory, nutritional content and antioxidants can be done by mixing various types of fruit juices. In the industry, fruit juice concentration aims to improve stability and reduce handling costs. Conventional concentration by evaporation can reduce the quality of fruit juice. Osmotic membrane distillation (OMD) is a processing alternative that can retain the uniqueness of fruit juices as much as possible due to low temperatures. This research aims to determine the best composition of mixed fruit juices and the optimum operating conditions for concentration with OMD. Optimization of the mixed fruit juice formulation consisting of dragon fruit, noni, and pineapple using Extreme Vertices Design and in DMO using central composite design (CCD) with variations in daw solution concentration (Potassium Sorbate) of 1, 1.75, and 2.5 M with feed temperature 35, 42.5, and 50 oC. The fruit juice mixture will be tested sensory in the form of taste, aroma, and hedonic taste and then the best formulation will be determined and then concentrated with DMO. Optimum operating conditions are determined based on the content of vitamin C, phenolic compounds, antioxidants, and concentration factors. Based on the experiment, the best-mixed fruit juice formulations were dragon fruit with 73.23%, noni fruit with 8.23%, and pineapple with 18.54%. Furthermore, the best operating conditions for OMD are the feed temperature of 46.51 oC and the concentration of 1 M draw solution.